Characterization of Soil Properties and the Implications for Landslide Occurrence in Rubanda District. - Ainamaani, Samuel (Kabale University, 2023)
Soil properties of major landslides that occurred on Tuesday 26th September 2017were analysed. A mudflow washed away Mfasha trading Centre, which hosts people mostly from Bufundi and Muko sub counties. In order to test the hypothesis that ‘soils at the landslide site are particularly ‘problem soils’ and thus prone to landslides’, the following analyses were undertaken: Dynamic Cone Penetration Test (DCP), particle size distribution and Atterberg limits. The liquid limits for all the test pits were all above the threshold of 25% indicating high expansion potential of the soils in this area. And from the plasticity charts the PI and LL results reveals that the soils are clay of high plasticity and this signals chances of landslides Soil particle distribution The clay fraction for the soil were above 10% threshold identified from the analysis of the soil samples from the respective test pits as shown in the table below, this explains higher possibilities of extreme expansion potential and hence susceptible to land slides The bearing capacity of soil was determined as 250.825 kN/M3.When compared with the safe Safe/allowable bearing capacity of Soft rock 440kN/M3, the bearing capacity of soil is too low indicating high chance of collapsible soil.